Two Methods for Auto-Organizing Personal Web History - Counts, Scott; Farnham, Shelly; Cheng, Lili (Association for Computing Machinery, Inc., 2003)
Two methods for automatically organizing personal web history were developed and evaluated, and compared to the Internet Explorer history. One method grouped visited web pages based on similarity of root URL and time co-occurrence. The second method started with the similarity ratings and further associated or dissociated web pages using an associative learning rule. In a preliminary experiment, participants reported that both methods organized their web history significantly more like their own mental organization of their web history than did IE history. Participants were also faster to revisit web pages using both organizations than when using IE history.